2023
DOI: 10.1080/07853890.2023.2197293
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index, metabolic syndrome and common urologic conditions: a cross-sectional study using a large multi-institutional database from the United States

Abstract: Introduction The study aims to determine whether body mass index (BMI), metabolic syndrome (MS) or its individual components (primary hypertension, type 2 diabetes mellitus and dyslipidemias) are risk factors for common urological diseases. Materials and methods Cross-sectional study with data collected on February 28, 2022 from the TriNetX Research Network. Patients were divided in cohorts according to their BMI, presence of MS (BMI > 30 kg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Other authors have also reported a similar association between prostate cancer and hypertension, although the precise cause‐and‐effect relationship of these findings remains unclear. 20 A prior study conducted by Ohwaki et al reported a link between diabetes and the diagnosis of high‐risk iPCa. 7 However, we did not notice any such association in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Other authors have also reported a similar association between prostate cancer and hypertension, although the precise cause‐and‐effect relationship of these findings remains unclear. 20 A prior study conducted by Ohwaki et al reported a link between diabetes and the diagnosis of high‐risk iPCa. 7 However, we did not notice any such association in our study.…”
Section: Discussionmentioning
confidence: 98%
“…There is evidence to suggest that elevated levels of serum LDL are causally linked to an increased risk of renal cancer, independent of TG and HDL levels [ 18 ]. Recent findings showed a significant positive association between dyslipidemia (elevated TG and decreased HDL) and ureteral cancer (odds ratio (OR) = 1.69; confidence interval (CI) = 1.51 - 1.90; P < 0.05) as well as bladder cancer (OR = 1.55; CI = 1.50 - 1.60; P < 0.05) [ 19 ]. The other comprehensive study called the Metabolic Syndrome and Cancer Project (Me-Can) 2.0 discovered a clear positive correlation between high CHOL levels and the risk of non-muscle invasive bladder cancer among men [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TriNetX platform has been used extensively in both adult and pediatric patient populations to report epidemiological outcomes and risk assessments in an array of pathologic settings. 13 15 This study followed the Strengthening the Reporting of Observational Studies in Epidemiology reporting guidelines. 16 Description of the database is further laid out in the Supplemental Methods .…”
Section: Methodsmentioning
confidence: 99%